PENGARUH TRANSPARANSI DAN AKUNTABILITAS DALAM PENGELOLAAN DANA DESA TERHADAP KINERJA PEMERINTAHAN DESA PAMAIT DI KABUPATEN BARITO SELATAN TAHUN 2022: The Effect of Transparency and Accountability in Management of Village Funds on the Performance of the Pamait Village Government in South Barito District Year 2022 - Kurniaty, Harlina (Pencerah Publik, 2023)
This research activity was carried out in order to find out the performance of the Village Government as the spearhead of the success of government programs so far, whether they have been properly implemented in a transparent and accountable manner, which ultimately aims to be felt and utilized by the people who really need them. The theory used for Transparency according to Mardiasmo (2006), Accountability according to Rasul (2002), Performance according to Mohammad Nahsun (2009) Research methods using Descriptive Quantitative Analysis with data collection techniques are Interviews, Questionnaires, Observation, and Documentation . This study uses 3 variables, namely Transparency (X1), Accountability (X2), and Performance (Y) of Pamait Village Government. The data analysis tool used is Multiple Linear Regression using SPSS Version 26. Effect of Accountability (X2) on Village Government Performance, showing that the t-count value is greater than t-table (2.111 > 1.996) and the significant value is less than 0.05 (0.038 <0.05), so it can be said that Transparency partially affects Village Government Performance in Pamait Village. So it can be concluded that H2 in this study Ho is rejected and Ha is accepted, meaning that the research hypothesis is correct. The Effect of Transparency (X1) and Accountability (X2) on Village Government Performance (Y) simultaneously. Based on the results of the regression analysis in the table, the value of Fcount < Ftable (2.251 < 2.72) and a significant value > 0.05 (0.113 > 0.05) is obtained. So it can be concluded that Ho is accepted and Ha is rejected, which means that Transparency and Accountability simultaneously do not significantly influence Village Government Performance, so it can be concluded that H3 in this study Ho is accepted and Ha is accepted, meaning that the research hypothesis is not correct.